Antioxidant, Anti-Inflammatory and Antiproliferative Effects of the Vitis vinifera L. var. Fetească Neagră and Pinot Noir Pomace Extracts - Balea, Ştefania Silvia; Pârvu, Alina Elena; Pârvu, Marcel; Vlase, Laurian; Dehelean, Cristina Adriana; Pop, Tiberia Ioana (Frontiers in Pharmacology, 2020)
It is well documented the pathophysiology of inflammation and oxidative stress generated during different types of cancers and anti-cancer treatments. Because grape pomace is a rich source of antioxidant compounds, the purpose of the study was to evaluate the antioxidant, anti-inflammatory and antiproliferative effects of fresh and fermented grape pomace extracts of Fetească neagră and Pinot noir cultivated in Romania. First, grape pomace phytochemical analysis and in vitro antioxidant test were performed. Secondly, the eﬀect of a seven-day pretreatment with grape pomace extracts on the turpentine oil-induced inflammation in rats was assessed by measuring total oxidative status, total antioxidant response, oxidative stress index, malondialdehyde, total thiols, nitric oxide and 3-nitrotyrosine. Thirdly, the antiproliferative properties were evaluated on human lung carcinoma (A549), human breast adenocarcinoma (MDA-MB-231), murine melanoma (B164A5) and keratinocyte (HaCat) cell lines. Fetească neagră and Pinot noir grape pomace extracts have a rich content of polyphenols and in vitro antioxidant effect. Fermented samples had higher polyphenol content, but fresh samples had better antioxidant activity. Pretreatment with grape pomace extracts reduced inflammation-induced oxidative stress in a concentration-dependent way, the fresh samples being more efficient. The malignant cells proliferation was inhibited by all grape pomace extracts, fermented Fetească neagră extracts having the stronger effect. Conclusion: fresh and fermented grape pomace extracts of Fetească neagră and Pinot noir cultivated in a Romanian region have antioxidant, anti-inflammatory and antiproliferative effects.